Pelatihan Kuliner untuk Masyarakat di Desa Wisata Boddia Kecamatan Galesong Kabupaten Takalar Provinsi Sulawesi Selatan - Ab, Ahmad (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Culinary Training for Communities in Boddia Tourism Village, Galesong District, Takalar Regency, South Sulawesi Province The purpose of this community service activity is to increase community knowledge and skills about culinary that can be an attraction in a tourist village. This training was aimed at housewives and young women in Boddia Tourism Village. The method used in this training is material presentation and hands-on practice. One of the things trained in this activity is culinary activities carried out in one of the tourist destinations in Takalar Regency, namely on Sanrobengi Island. The positive impact of this community service activity is that housewives and young women can fill their spare time by making cooking creations at home. This is because culinary is one of the drivers of creative economy entrepreneurship which can certainly increase community income. The results of the activity showed that the participants were very satisfied with this training activity, including the service of the activity committee, the quality of the training material provided, the ability of the resource person in providing material, the suitability of the material provided to the needs of the trainees, and the participants' satisfaction with the implementation of culinary training.